Impact of CLAD Phenotype on Survival After Lung Retransplantation: A Multicenter Study. Issue 8 (30th April 2015) - Verleden, S. E.; Todd, J. L.; Sato, M.; Palmer, S. M.; Martinu, T.; Pavlisko, E. N.; Vos, R.; Neyrinck, A.; Van Raemdonck, D.; Saito, T.; Oishi, H.; Keshavjee, S.; et al.
<x xml:space="preserve">Abstract</x> Chronic lung allograft dysfunction (CLAD) remains a major problem after lung transplantation with no definitive treatment except redo lung transplantation (re‐LTx) in selected candidates. However, CLAD is not a homogeneous entity and different phenotypes exist. Therefore, we aimed to evaluate the effect of CLAD phenotypes on survival after re‐LTx for CLAD. Patients who underwent re‐LTx for respiratory failure secondary to CLAD in four LTx centers between 2003 and 2013 were included in this retrospective analysis. Bronchiolitis obliterans syndrome (BOS) and restrictive CLAD (rCLAD) were distinguished using pulmonary function, radiology and explant lung histopathology. Patient variables pre‐ and post‐re‐LTx were collected and analyzed. A total of 143 patients underwent re‐LTx for CLAD resulting in 94 BOS (66%) and 49 rCLAD (34%) patients. Unadjusted and adjusted survival after re‐LTx for rCLAD was worse compared to BOS (HR = 2.60, 1.59–4.24; p < 0.0001 and HR = 2.61, 1.51–4.51; p = 0.0006, respectively). Patients waiting at home prior to re‐LTx experienced better survival compared to hospitalized patients (HR 0.40; 0.23–0.72; p = 0.0022). Patients with rCLAD redeveloped CLAD earlier and were more likely to redevelop rCLAD. Survival after re‐LTx for rCLAD is worse compared to BOS. Consequently, re‐LTx for rCLAD should be critically discussed, particularly when additional peri‐operative risk factors are present.